Descobrindo conceitos cinemáticos e dinâmicos através da interatividade e da leitura: uma prática investigativa em física - Santos Júnior, Marcelo dos (2019)
The teaching of physics centered on the memorization of formulas and repetitive exercises has washed away the predominance of a didactic-pedagogical procedure that left the research scope of this science in a secondary or even non-existent character. And, faced with new educational requirements with an emphasis on skills and competency development, the memory focus on physics has become inefficient. In order to follow an investigative approach, it was decided to elaborate a didactic sequence in Jorde's investigative perspective to two classes of the 1st year of high school. In order to contemplate this educational itinerary, didactic practice was divided into seven stages anchored in real, virtual experiments and in reading through problem situations. With interactivity and collective discussion contemplating such stages, Lev Vygotsky's theory of learning was used as theoretical support. As educational practice also used previous knowledge and organizers to achieve the objectives of the research, the theory of David Ausubel was also used in an integrated way. The last part of the methodology basically consisted of contemplating the final objective of the didactic product, which basically consisted in the individual construction of a conceptual map interconnecting kinematic and dynamic concepts through the relation between Newton's first two laws and the causes of accelerated and / or rectilinear. Through qualitative and quantitative data it was possible to perceive to extract evidence of significant learning from the student body, both during and after the research. The results analyzed separately from each class, as well as the comparative results, showed an indicative of effective learning of kinematic and dynamic concepts.